2009
DOI: 10.3233/nre-2009-0508
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of functional outcomes in stroke rehabilitation for Chinese population: A cluster analysis

Abstract: The objectives of study were to identify longitudinal ADL profiles and to investigate profiles characteristics of participants in stroke rehabilitation programme. 496 stroke rehabilitation records in one year were retrieved. Patients' demographics, admission scores of Cantonese version of Mini-mental State Examination and line cancellation test were retrieved. Chinese version of the Modified Barthel Index (MBI-C) records for the first four successive weeks were also obtained for cluster analysis. Four function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The study findings were similar to those of previous studies. 10 , 22 , 23 , 36 38 The results of these studies confirmed that older adults had lower FIM scores. Additionally, the findings of these studies confirmed that a higher FIM score on admission is associated with higher scores on discharge.…”
Section: Discussionsupporting
confidence: 69%
“…The study findings were similar to those of previous studies. 10 , 22 , 23 , 36 38 The results of these studies confirmed that older adults had lower FIM scores. Additionally, the findings of these studies confirmed that a higher FIM score on admission is associated with higher scores on discharge.…”
Section: Discussionsupporting
confidence: 69%
“…The present study showed that the groups of patients who had the greatest benefit from stroke rehabilitation program were those with admission categories of MFAC 3 to 5 in terms of MRMI efficiency and those with admission categories of MFAC 4 to 5 in terms of MBI efficiency. The present study echoes with Louie’s study 7 that patients with stroke with moderate disability on admission presented the best rate of improvement in functional outcomes on discharge. Under resource constraints, stroke rehabilitation teams have to stratify patients with stroke as soon as possible so as to allocate suitable resources, such as therapy sessions or LOS in hospital, to patients with stroke.…”
Section: Discussionsupporting
confidence: 87%
“…Early stratification of patients with stroke is useful for clinicians to recognize patients’ possible functional outcomes, level of disability and requirement for social support so as to facilitate early discharge plan and reduce avoidable length of stay (LOS) in hospital. Stratification in clinical setting is usually based on admission functional scores such as Functional Independence Measure (FIM TM ), 5 Barthel Index (BI), 6 Modified BI (MBI), 7 and classification system such as Inpatient Rehabilitation Facility-Case-Mix Group (IRF-CMG). 8 However, these assessment tools are quite time-consuming and require a special training to complete the full score.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It was shown that patients with stroke who had as much practice as possible within 6 months after stroke onset could achieve the best functional outcome. [5][6][7] In Hong Kong, under the service model of Hospital Authority, patients would be referred to ambulatory services, such as geriatric day hospital, or domestic physiotherapy services to continue their stroke rehabilitation after discharge from hospital. However, some patients could not attend ambulatory services due to various di±culties, such as transportation and absence of carers.…”
Section: Introductionmentioning
confidence: 99%